2006
DOI: 10.14429/dsj.56.1939
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Initial Stability of an FSAPDS Projectile

Abstract: For a spinning projectile, the initial stability condition is 2 = 1+ (4 K 3 / K 2 2 ) > 0. In the present study, this condition has been modified for the malalignments arising due to pressure gradient and damping moment for an FSAPDS projectile. The equations of motion are established for the first phase of motion. A mathematical model for the first phase of motion has been developed. The effect of perturbation on the trajectory and stability of motion are discussed. It is proved that if 3 K (a parameter appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The propellant gases following the projectile, exert pressure on the projectile and affect its trajectory and stability. The effect of these forces has been discussed in the earlier work by the authors 2 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The propellant gases following the projectile, exert pressure on the projectile and affect its trajectory and stability. The effect of these forces has been discussed in the earlier work by the authors 2 .…”
Section: Introductionmentioning
confidence: 93%
“…The stability of the projectile motion in phase I has been discussed with modified stability parameter and it was observed that the motion remains stable due to perturbation caused by pressure gradient and damping moment 2 . The modified stability parameter has been discussed due to shock wave and mechanical forces exerted on the projectile body.…”
Section: Stability Of Motionmentioning
confidence: 99%
“…The equations for stability in projectile-fixed frame are the same as those in phase II 2 . The changed values of K i (i=1,2,3,4,5,6) modified the stability parameter 13 .…”
Section: Stability Of Motionmentioning
confidence: 99%